2021
DOI: 10.1186/s12880-021-00579-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation patterns in medicated versus medication-naïve adults with attention-deficit hyperactivity disorder during fMRI tasks of motor inhibition and cognitive switching

Abstract: Background Adult-attention-deficit-hyperactive-disorder (ADHD) is often unrecognized condition. FMRI examination along with neuropsychological testing might strengthen the diagnosis. We hypothesized that ADHD-adults with and without medication would show different fMRI pattern compared to healthy controls while testing tasks of motor inhibition and cognitive switching. Methods 45 subjects in three age-matched groups: (1) controls, (2) ADHD-adults u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Furthermore, this effect was modulated by the working memory score from the BRIEF-A measure of executive functions. The finding of this association in the striatum is consistent with prior studies noting stimulant treatment effects in the striatum of patients with ADHD (Berberat et al, 2021;Bouziane et al, 2019;Schrantee et al, 2016;Schweren et al, 2016;Vaidya et al, 1998) as well as two studies reporting that pre-treatment structural (Chang et al, 2021) or functional (Rode et al, 2023) neuroimaging measures of the striatum were associated with stimulant treatment efficacy in ADHD. Further, higher pre-treatment Working Memory scores were associated with greater treatment efficacy across all participants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, this effect was modulated by the working memory score from the BRIEF-A measure of executive functions. The finding of this association in the striatum is consistent with prior studies noting stimulant treatment effects in the striatum of patients with ADHD (Berberat et al, 2021;Bouziane et al, 2019;Schrantee et al, 2016;Schweren et al, 2016;Vaidya et al, 1998) as well as two studies reporting that pre-treatment structural (Chang et al, 2021) or functional (Rode et al, 2023) neuroimaging measures of the striatum were associated with stimulant treatment efficacy in ADHD. Further, higher pre-treatment Working Memory scores were associated with greater treatment efficacy across all participants.…”
Section: Discussionsupporting
confidence: 88%
“…One more study compared responders versus non-responders and found that responders had higher incentive salience and hedonic experience scores than non-responders and that such scores correlated with resting-state functional magnetic resonance imaging (fMRI) connectivity in the ventral striatum (Rode et al, 2023). The findings that pre-treatment striatal structure and function were related to treatment response are consistent with considerable structural and functional imaging evidence pointing toward the role of striatal regions associated with receiving ADHD stimulant medication across child, adolescent, and adult ADHD cohorts (Berberat et al, 2021; Bouziane et al, 2019; Schrantee et al, 2016; Schweren et al, 2016; Vaidya et al, 1998).…”
Section: Introductionsupporting
confidence: 77%
“…This study suggests a decentralized organization (line-like topology) in the frontoparietal attention network in children with ADHD in contrast to the more centralized organization (star-like topology) in typically developing (TD) children. Another fMRI study found that drug-naïve individuals with ADHD show more activation of the bilateral inferior parietal lobe during inhibition, measured by stop-signal task, and less activation in the left parietal cortex during shifting attention, measured by switch task (Berberat et al, 2021). Kolodney et al (2020) found that during an inhibitory control task (go/no-go), in individuals with ADHD with lower symptoms, the cooperation of the intraparietal sulcus (IPS) and the right inferior frontal gyrus (IFG) is increased.…”
Section: Functional Magnetic Resonance Imaging (Fmri) Studiesmentioning
confidence: 99%
“…The activity of left IPL decreases during cocktail-party conditions (Salmi et al, 2020) and switching tasks (Berberat et al, 2021) but increases during fearful face mimicry (Lindholm et al, 2019). The left parietal region is not only involved in the obvious symptoms of ADHD, such as inattention, impulsivity, and hyperactivity but also working memory and emotional perception, such as fear and joy.…”
Section: The Left Parietal Lobementioning
confidence: 99%
“…The British Association of Psychopharmacology (Narbona, 1997) points out that both genetic and environmental factors can play an important role in alterations in brain circuits. The approaches used to study ADHD are divided into genetic, neurochemical, structural, and functional (Berberat et al, 2021). Diagnosis, due to the absence of specific biomarkers common to the entire spectrum of patients, evaluation and treatment are based on clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%